Analisis Keterampilan Berpikir Kreatif Peserta Didik Kelas XI Fase F SMAN 4 Padang - Hayatur Rahmi; Rahmadhani Fitri (LP2M UIN Ambon, 2026)
Creative thinking skills are one of the essential twenty-first-century competencies that should be developed in Biology learning. However, students' creative thinking skills have not yet developed optimally. This study aimed to describe the creative thinking skills of Grade XI Phase F students at SMAN 4 Padang based on the indicators of curiosity, fluency, originality, elaboration, and flexibility. This study employed a quantitative descriptive research design conducted during the first semester of the 2025/2026 academic year at SMAN 4 Padang. The sample consisted of all Grade XI Phase F students selected using the total sampling technique. Data were collected using an essay test and analyzed descriptively through mean scores and percentages for each indicator. The results showed that the students' creative thinking skills had an average score of 55.04, indicating a low level of creative thinking skills. Among the five indicators, elaboration achieved the highest average score (58.84), whereas fluency obtained the lowest (49.58). The findings are expected to serve as baseline data for designing more student-centered learning strategies to foster students' creative thinking skills in Biology learning.